RANCANG BANGUN APLIKASI MENGENAL JENIS KECERDASAN DAN BAKAT SISWA BERBASIS ANDROID - Tina Puspita; siswanto siswanto; Ricky Zulfiandry (Jurnal Media Infotama, 2022)
ABSTRACT The State 17 Junior High School in Bengkulu City is one of the junior high schools in Bengkulu Province, the same as junior high schools in general whose education is taken within 3 years of study, starting from grades VII and IX. This school is located at Wr. Supratman Street, Pematang Governor, Muara Bangkahulu District. The subject of this research is the design of applications to recognize the intelligence and talent of Android-based students on Android devices. While the research subjects were students of class 1X State Junior High School 17 Bengkulu City. State Junior High School 17 Bengkulu City for class 1X consists of 2 classes, with a total of 64 students. The large number of students taken for testing refers to a statement that explains that "at least 20% for the population is considered small". However, the 20% amount is still considered insufficient. So that the taking of the number of students follows the rules set by students, which is between 30-500 students. So that taken half of the total number of 32 students. This application to identify the type of intelligence and talent of students based on Android is an application built using Android Studio with the Java programming language, PHP and MySQL database. This application has 2 different interfaces, for the admin side can access web-based applications on a predetermined web link, while for the user side can access android-based applications that can be installed on each android smartphone. Based on testing using Usability Testing, the results obtained are the level of ease of users to complete basic tasks when the user first sees or deals with the existing system, the level of efficiency of the application according to the purpose of the application and the features contained in the application make it easier for users to run the application, the application is easy to remember, with a colorful menu display and the features in the application make it easier for users to manage or run applications, the security level in the application is quite adequate when installing the application there are some devices that experience errors because they do not support the minimum operating system used, and user satisfaction with the application, satisfied with the information provided and the security provided by the application Keywords: Applications, Types of Intelligence and Talent, Students, Android